A Short, Multimodal Activity Break Incorporated Into the Learning Context During the Covid-19 Pandemic: Effects of Physical Activity and Positive Expressive Writing on University Students' Mental Health—Results and Recommendations From a Pilot Study - Marschin, Verena; Herbert, Cornelia (Frontiers in Psychology, 2021)
Physical inactivity, sedentary behavior and mental ill health, due to high levels of perceived stress or self-reported depressive symptoms, are highly prevalent among university students. There are concerns that these behaviors and mental symptoms have significantly increased during the current Covid-19 pandemic, partly because academic life has changed considerably from face-to-face communication to e-learning and studying at home. Self-regulation and physical activity are hard to maintain during pandemic lockdowns. Short activity breaks could be helpful to avoid physical inactivity and sustain mental health. The breaks should comprise short and easy-implementable physical activity exercises that can be integrated into the learning context. Moreover, cognitive interventions, such as writing about positive events and feelings might help as coping strategy for self-regulation during study breaks. This study investigated and compared the effects of a physical activity intervention and a cognitive intervention (positive expressive writing) on mental health among university students. Both interventions are particularly suitable for use at home. N = 20 university students, studying in Germany, were assigned to a physical activity group or a cognitive intervention group. The physical activity intervention consisted of a mix of physical exercises including endurance exercises, muscular strength, relaxation, and ballroom dance movements. The interventions were carried out guided, once a week, for five to ten minutes at the beginning of classes. The effects of group x time showed no significant interaction on self-reported perceived stress, mood, quality of life (QoL) assessed online and compared at the beginning of the term before the intervention (T0) and at the end of the term after the intervention (T3). However, the physical activity group reported a similar physical activity level per day over time, while the cognitive intervention group showed a decrease in physical activity from T1 to T3. Low-dose, short physical activity interventions as well as cognitive interventions consisting of positive expressive writing could buffer university students’ perceived stress, mood, and QoL across the term. Moreover, both interventions seem to be promising in buffering the negative side effects of stress during the Covid-19 pandemic.